Odpowiedź :
a)
[tex]3x - 2 = 5x + 1 \\ - 2x = 3 \\ x = - \frac{3}{2} = - 1.5[/tex]
b)
[tex] \frac{6x - 3}{3} + 2 = 0 | \times 3 \\ 6x - 3 + 6 = 0 \\ 6x = - 3 \\ x = - \frac{3}{6} = - \frac{1}{2} = - 0.5[/tex]
Pierwsze równanie
[tex]\frac{6x-3}{3}+2=0 \ \ |\cdot3\\\\6x-3+6=0\\\\6x+3=0\\\\6x=-3 \ \ |:6\\\\\boxed{x=-0,5}[/tex]
Drugie równanie
[tex](x-1)(2x+2)=2x^2\\\\2x^2+2x-2x-2=2x^2\\\\2x^2-2=2x^2\\\\2x^2-2x^2=2\\\\0=2\\\\\boxed{x=\O}[/tex]
Równanie sprzeczne, nie posiada rozwiązania.
3)
[tex]3x-2=5x+1\\\\3x-5x=1+2\\\\-2x=3 \ \ |:(-2)\\\\\boxed{x=-1,5}[/tex]